Common issues raised during the quality assurance process of WHO guidelines: a cross-sectional study - Teegwendé V. Porgo; Mauricio Ferri; Susan L. Norris (BMC, 2018)
Abstract Background In 2007, WHO established the Guidelines Review Committee (GRC) to ensure that WHO guidelines adhere to the highest international standards. The GRC reviews guideline proposals and final guidelines. The objectives of this study were to examine the rates of and reasons for conditional approval and non-approval of documents submitted for the first time to the GRC, and calculate the time intervals and numbers of submissions to achieve approval for documents conditionally approved or not approved at first submission. Methods All initial submissions to the GRC between 2014 and 2017 were examined. Data were extracted from the GRC's records of written comments and discussions. Results Of a total of 85 proposals and 88 final guidelines, 32 (37.6%) proposals and 37 (42.0%) final guidelines were conditionally approved, and 15 (17.6%) proposals and 28 (31.8%) final guidelines were not. For both conditionally approved and not approved proposals, the most frequent reasons were suboptimal composition or inadequate description of the guideline contributor groups (in all proposals), followed by inadequate formulation of key questions (in 90.6% of conditionally approved proposals and all not approved proposals). For both conditionally approved and not approved final guidelines, the most frequent reasons were problems with recommendations (in all final guidelines), followed by inappropriate methods for evidence retrieval or an inadequate description thereof (in all conditionally approved final guidelines and 75.0% of not approved final guidelines). The median time to achieve approval was 2 months for proposals and 1-2 months for final guidelines. The median number of submissions was 2 for proposals and 2-2.5 for final guidelines. Conclusion The GRC implements a rigorous quality assurance process and identifies problems with a significant percentage of initial submissions. WHO needs to continuously evaluate its guideline development processes to inform effective quality improvement measures and optimise the quality of its guidelines.